A Novel DNA Computing Based Encryption and Decryption Algorithm - UbaidurRahman, Noorul Hussain; Balamurugan, Chithralekha; Mariappan, Rajapandian (Procedia computer science, 2015)
Lot of techniques and systems has been developed based on modular arithmetic cryptography for encryption and decryption. However, these techniques are broken using DNA cryptography techniques and methods. DNA Cryptography is a new instinctive cryptographic field that has emerged from the research of DNA computing. Some algorithms that are available in DNA Cryptography have limitations in that they still use modular arithmetic cryptography at some of their steps or they are biological laboratory experiment based which is not suitable in the digital computing environment. To overcome this lacuna, we describe a novel, secure, unique and dynamic DNA based encryption and decryption algorithm and also provide an analysis of its performance.